2010
DOI: 10.1002/micr.20739
|View full text |Cite
|
Sign up to set email alerts
|

Cold ischemia in microvascular breast reconstruction

Abstract: Cold ischemia facilitates breast reconstruction by allowing the surgical team to alternate breaks during the operation. This helps reduce surgeon fatigue and is well tolerated by the flap. Thus, we believe that the use of cold ischemia is safe and advantageous in microvascular breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Therefore, leaving flaps in cold ischemia can provide extra time. Lee and Lee [12] also reported that cold ischemia time up to 5 hours is safe, and is not associated with an increased risk of flap complications. Consequently, we cooled the flap, allowing us to prolong the ischemia time without compromising the success of the operation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, leaving flaps in cold ischemia can provide extra time. Lee and Lee [12] also reported that cold ischemia time up to 5 hours is safe, and is not associated with an increased risk of flap complications. Consequently, we cooled the flap, allowing us to prolong the ischemia time without compromising the success of the operation.…”
Section: Discussionmentioning
confidence: 94%
“…Animal and experimental studies have shown that elevated flaps can be kept in cold ischemia to provide a longer, yet safe, time to use the free flaps [12][13][14][15]. In addition, it is common to use hypothermia to prolong the amount of tolerated ischemia time in solid organ transplantation, such as the liver and kidney.…”
Section: Discussionmentioning
confidence: 99%